Análisis Silvigénico de los Bosques Húmedos Tropicales del Parque Nacional La Cangreja, Pacífico Central de Costa Rica - Acosta-Vargas, Luis Guillermo (Instituto Tecnológico de Costa Rica, 2011)
Information from six sites with long - term monitoring plots at La Cangreja National Park, Central Pacific of Costa Rica, monitored by 13 years of (1998 - 2011) was analyzed to determine the forest ́s sylvigenetic development. On 2011, averages values to the forest were an nual mortality 1,88±0,62% , annual recruitment 1,5±0,34%, N/ha 555±52 and G/ha 39,6±6,0 m 2 /ha. Correspondence, cluster and SHE Analysis determined that there are 3 kinds of forest on the six sites studied. a.) Logged forest: on Phase III dynamic of Sylvigenesis; G 38,2 m 2 /ha, N/ha 560, heigh t 34 m, annual mortality 2,05%, annual recruitment 1,41%. In the future, there is expected that this forest keeps the actual structure and floristic composition. b.) Mature secondary forest: on Phase III homeostat ic of Sylvigenesis; G 53,01 m 2 /ha, N/ha 568, height 31,4 m, annual mortality1,2%, annual recruitment 1,76%..The future of this forest will depend of Ficus insipida mortality. If they die and decomposed standing up, it would give the chance to saplings and low diameter class to close the gaps, but if they were fallen by winds or landslide, the gaps size would be bigger and Sylvigenesis will go back to the Phase II or Phase I. c.) Intermediate maturity of secondary forest: on Phase III dynamic of Sylvigenesis G 31 , 75 m 2 , N/ha 522, height 29,4 m, annual mortality 1,88%, annual recruitment 1,64%. In the future there is expected that pioneer species would continue diying, and gaps will be closed by the established regeneration of partial tolerant shade species in to low diameter class.
Proyecto de Graduación (Licenciatura en Ingeniería Forestal). Instituto Tecnológico de Costa Rica, Escuela de Ingeniería Forestal, 2011.
Keywords: Extención forestal; Fertilización forestal; Genética forestal; Cobertura forestal